Konsep Pemikiran Ekonomi Islam Imam Al Ghazali - Muhamad Faiz Arrafi; Cita Sary Dja'akun; Marwini Marwini (LABATILA : Jurnal Ilmu Ekonomi Islam, 2022)
This article describes Al-Ghazali's thoughts in the field of economics through his monumental work Ihya 'Ulum Al-Adin. Al-Ghazali explained thoroughly the aspects of substance in Islamic economics. Al-Ghazali lived in an era where rulers tried to justify their actions by asking religious leaders for fatwas with the intention of justifying these actions. Al-Ghazali entered the second phase in the history of Islamic economic thought. The second phase started in the 11th century until the 15th century. In this second phase many faced political realities marked by the many acts of corruption among the authorities and accompanied by moral decadence which resulted in a wider gap between the rich and the poor. Al-Ghazali implemented an Islamic economic system using a Sufism approach, because during his lifetime it was difficult for people who were rich, powerful, and full of prestige to accept the fiqh and philosophical approach in believing in Yaum al-Hisab (the Day of Judgment).